38 nooses : Lincoln, Little Crow, and the beginning of the frontier's end - Berg, Scott W. (Pantheon Books, 2012)
"38 Nooses" details the events surrounding the 1862 uprising of the Dakota Indians led by Little Crow within the larger context of the Civil War, the history of the Dakota people, and the subsequent United States-Indian wars.